Effect of exercise on athletes performing in fencing uniforms: Methodology and preliminary results of the use of infrared thermography to detect the thermal behaviour of fencers - Lamberti, G.; Leccese, F.; Salvadori, G.; Fantozzi, F. (Applied Sciences, 2020)
In recent times, infrared thermography has been often applied to sport science, in order to evaluate athletes` performance in relation to their thermal behaviour. As there is a lack of studies for the sport of fencing, this paper aims to provide preliminary results showing the thermal behaviour of fencers of different competitive level and to provide a methodology for its assessment. In particular, thermal images were acquired before, during and after the training, as well as the metabolic rate and the rate of perceived exertion, for eight fencers with different competitive levels (international/national/veteran). Results showed that in moderate environments there was any correlation between the environmental parameters and temperature trend on athletes` bodies, while competitive level and thermal behaviour were connected. The presence of thermal asymmetries was also detected. In general, from these preliminary results, professional athletes presented the same temperature trend. Therefore, further studies should be carried out in order to investigate these findings on a larger sample of elite athletes, as their thermal response may be important for improving their performance.